PERKEMBANGAN ORGANISASI PEMUDA PANCASILA DI BANDA ACEH TAHUN 1984-2016 - Syahrul Indra; Teuku Abdullah; Zainal Abidin (Universitas Syiah Kuala, 2017)
ABSTRACTIn accordance with the above title, which is